Cardiorespiratory Fitness and Long-Term Survival in “Low-Risk” Adults - Barlow, Carolyn E. (Blackwell Publishing Ltd, 2012)
BACKGROUND: We sought to establish whether cardiorespiratory fitness had important implications for long-term cardiovascular risk among individuals classified as low risk by the Framingham Risk Score (10-year coronary heart disease risk <10%). Prognostic factors of long-term cardiovascular risk are needed for low-risk subjects who make up the largest percentage of the US population. METHODS AND RESULTS: The study population was composed of men and women, 30 to 50 years of age, who had a baseline medical exam at the Cooper Clinic, Dallas, TX, between 1970 and 1983. Eligible individuals were defined as at low risk for coronary heart disease by Framingham Risk Score at the time of study entry and had no history of diabetes (n=11 190). Cardiorespiratory fitness was determined by maximum graded exercise treadmill tests. Over an average 27±2-year period, 15% of low-fit (quintile 1) compared to 6% of high-fit (quintile 5) individuals died (P<0.001). A 1–metabolic equivalent level increase in baseline fitness was associated with an 11% reduction in all-cause deaths and an 18% reduction in deaths due to cardiovascular disease (CVD) after adjustment for age, sex, body mass index, systolic blood pressure, total cholesterol, blood glucose levels, smoking, and early family history of coronary disease. There was an incremental decrease in CVD risk with increasing fitness quintile, such that the high fit had the lowest adjusted 30-year CVD mortality rate (hazard ratio 0.29, 95% CI: 0.16–0.51) compared to the low fit. CONCLUSIONS: Cardiorespiratory fitness is associated with a significant reduction in long-term CVD among individuals identified as low risk by Framingham Risk Score. These data suggest that preventive lifestyle interventions geared to optimize cardiorespiratory fitness, even among a “low-risk” subset, should be considered to improve CVD-free survival. (J Am Heart Assoc. 2012;1:e001354 doi: 10.1161/JAHA.112.001354.)